2002
DOI: 10.1046/j.1537-2995.2002.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of normal prion protein expression on human, rodent, and ruminant blood cells by using a panel of prion antibodies

Abstract: Different animal species have unique patterns of expression of PrPC on blood cell types, with none equivalent to the human pattern. This needs to be considered when extrapolating from animal models of blood-borne transmissible spongiform encephalopathy infectivity, particularly in regard to the risk assessment of potential variant CJD spread within the human population. The relationship between PrP distribution and infectivity distribution in blood needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 60 publications
3
26
0
Order By: Relevance
“…The presence of PrP C in blood has been documented [14], [15], and is confirmed by our own unpublished observations. To produce one liter of milk, about 400 to 500 liters of blood must pass through the udder of a cow.…”
Section: Discussionsupporting
confidence: 84%
“…The presence of PrP C in blood has been documented [14], [15], and is confirmed by our own unpublished observations. To produce one liter of milk, about 400 to 500 liters of blood must pass through the udder of a cow.…”
Section: Discussionsupporting
confidence: 84%
“…The reaction to PrP C on bovine leukocytes was weaker with both mAbs (E12/2 and 6H4), probably due to the lower expression of PrP C on the surface of bovine leukocytes. Barclay et al [45] also reported that PrP C appeared to be less widely distributed on the blood cells of mice, cattle and sheep compared to PrP C expressed on human blood cells. Beside the level of PrP C expression, the conformation and/or glycosylation state may affect the results as well [45].…”
Section: Discussionmentioning
confidence: 99%
“…Barclay et al [45] also reported that PrP C appeared to be less widely distributed on the blood cells of mice, cattle and sheep compared to PrP C expressed on human blood cells. Beside the level of PrP C expression, the conformation and/or glycosylation state may affect the results as well [45]. It was previously observed that bovine lymphocytes only express a diglycosylated isoform of PrP C [46].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have attempted to infer the likely distribution of PrP Sc and infectivity in blood components by studying the distribution of PrP c [47]. However, this approach should be treated with caution on two main grounds: first, PrP c is widely distributed in many tissues throughout the body, but only some of these tissues are capable of supporting infectivity and/or PrP Sc [2]; second, there is remarkable interspecies variation in the distribution of PrP c in blood components [48], but these differences do not appear (admittedly on the basis of incomplete data) to reflect interspecies differences in infectivity and/or PrP Sc distribution in blood components, at least in experimental models of prion disease (Table 5).…”
Section: Evidence For Infectivity In Blood In Prion Diseasesmentioning
confidence: 99%